2015
DOI: 10.3109/19401736.2015.1053125
|View full text |Cite
|
Sign up to set email alerts
|

Description and comparison of two economically important fish species mitogenomes: Prochilodus argenteus and Prochilodus costatus (Characiformes, Prochilodontidae)

Abstract: Prochilodus spp. are important Brazilian freshwater migratory fishes with substantial economic and ecological importance. Prochilodus argenteus and Prochilodus costatus are morphologically similar and a molecular species delimitation is impaired due to high degree of sequence identity among the available genetic markers. Here, the complete mitochondrial genome of P. argenteus and P. costatus and their comparison to the mitogenome of P. lineatus are described. The three species displayed a similar mtDNA annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In the Brazilian Shield, Prochilodus costatus share the same mitochondrial cluster with P. lineatus (lineage 8), which again corroborates the molecular phylogeny (Melo et al, 2016a ) and a mitogenome analysis (Chagas et al, 2015 ). Analyzed specimens of P. costatus from Rio Pandeiros/São Francisco are remarkably distant (~2,500 linear km) from analyzed specimens of P. lineatus from Rosario in Argentina.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the Brazilian Shield, Prochilodus costatus share the same mitochondrial cluster with P. lineatus (lineage 8), which again corroborates the molecular phylogeny (Melo et al, 2016a ) and a mitogenome analysis (Chagas et al, 2015 ). Analyzed specimens of P. costatus from Rio Pandeiros/São Francisco are remarkably distant (~2,500 linear km) from analyzed specimens of P. lineatus from Rosario in Argentina.…”
Section: Discussionsupporting
confidence: 81%
“…Prochilodontids represent a good model to address such questions because much research on population genetics and phylogeography have provided valuable intraspecific genetic information (Sivasundar et al, 2001 ; Turner et al, 2004 ; Hatanaka et al, 2006 ; Carvalho-Costa et al, 2008 ; Melo et al, 2013 ; Rueda et al, 2013 ; Ferreira et al, 2017 ; Machado et al, 2017 ; Sales et al, 2018 ). Furthermore, recent barcoding studies in focal regions (i.e., using endemic species) have generated a robust mitochondrial database for Prochilodus (e.g., Carvalho et al, 2011 ; Rosso et al, 2012 ; Pereira et al, 2013 ; Chagas et al, 2015 ; Díaz et al, 2016 ) that, if combined, might be useful for species-level comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…The sex ratio between P. costatus females and males is 1:1.5 (Arantes, Santos, Rizzo, Sato, & Bazzoli, 2011 ). Because P. costatus has a very high phylogenetic similarity to P. lineatus (Chagas et al 2016 ; Melo et al 2018 ), and as already reported by Castro & Vari (2004), species of the genus Prochilodus bear a very similar resemblance in morphology and behavior. According to Arantes et al ( 2011 ), the mean total length is 35.5 ± 11.2 cm, the mean weight is 761.9 ± 692.0 cm females, and a sex ratio is estimated in 1:1.5 for P. costatus populations of São Francisco River basin.…”
Section: Methodsmentioning
confidence: 60%
“…Both complete and nearly complete mitochondrial genomes are available for characiform fishes (e.g., Landínez‐García et al, 2016; Nakatani et al, 2011; Saitoh et al, 2003), but a combined phylogenetic analysis has not been conducted yet. For Prochilodus , complete mitogenomes have been generated for P. argenteus , P. costatus , and P. lineatus , all presenting similar gene annotations and phylogenetic analyses supporting the monophyly of the genus (Chagas et al, 2016; Carmo et al, 2016). However, these studies did not include more than one specimen to test the monophyly of the species nor did they use other prochilodontids.…”
Section: Introductionmentioning
confidence: 83%